Reconstructing Europe After WWII: Logistical Dimensions of the Marshall Plan (April 1948‒December 1951) (American Journal of Management, 2025)
The Marshall Plan, launched after WWII, was a North American economic aid program that had a major impact on contemporary history. It revitalized Europe’s infrastructure and industries and encouraged cooperation between nations, laying the foundations for the future European Union. The aim was not only to support economic recovery but also to stem the spread of communism against the backdrop of the Cold War by politically and economically stabilizing the countries of Western Europe. One often-overlooked aspect of the Marshall Plan’s success lies in its logistical dimensions. Faced with destroyed transport infrastructure and damaged ports, the United States introduced modern supply chain management methods into Western Europe to efficiently coordinate the delivery of goods, particularly foodstuffs. While the legacy of the Marshall Plan influences current approaches to operations management, it remains little discussed about its geopolitical dimensions. This paper suggests that studying the logistics dimensions of the Marshall Plan could enrich our understanding of supply chain dynamics.
Keywords: management; geopolitics; logistics; Marshall Plan; post-WWII reconstruction; supply chains